2006
DOI: 10.1055/s-2006-944970
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic retrograde cholangiopancreatography after pancreaticoduodenectomy for benign and malignant disease: indications and technical outcomes

Abstract: ERCP plays an important role in the management of postpancreatic surgery problems including biliary and anastomotic strictures, and should be the modality of choice. However, surgical technique may make the afferent limb inaccessible, and the ductal anastomosis difficult to identify in patients with some types of pancreaticoduodenectomy. Closer collaboration between surgeon and endoscopist may allow alterations in surgical technique to improve postoperative ERCP success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 4 publications
1
48
1
Order By: Relevance
“…In our institution, we often consider EUS-guided MPD drainage before ERP in patients with a pancreaticoduodenectomy due to the higher reported success rate with this procedure [23][24][25][26][27]. The option of EUS-guidance should be considered relatively early in a difficult cannulation as same-day ERP was associated with a higher rate of technical failure [8].…”
Section: Suggested Algorithmic Approach To Eus-guided Pancreaticobilimentioning
confidence: 99%
“…In our institution, we often consider EUS-guided MPD drainage before ERP in patients with a pancreaticoduodenectomy due to the higher reported success rate with this procedure [23][24][25][26][27]. The option of EUS-guidance should be considered relatively early in a difficult cannulation as same-day ERP was associated with a higher rate of technical failure [8].…”
Section: Suggested Algorithmic Approach To Eus-guided Pancreaticobilimentioning
confidence: 99%
“…Before BAEs were introduced, CEs had traditionally been used for ERCP in patients with PD. Farrell et al [6] reported that they routinely started with a side-viewing duodenoscope, and if it failed, that they would switch to a gastroscope or colonoscope. In 29 patients with PD, their rate of successful endoscope insertion was 93.1 % and technical success was 62 %.…”
Section: Discussionmentioning
confidence: 99%
“…Early case series have reported some results of ERCP with conventional endoscopes (CEs) in patients with PD. The authors usually used a side-viewing duodenoscope and forward-viewing endoscopes for ERCP in these patients [6][7][8]. These studies reported relatively high success rate for biliary indications but poor success rate for pancreas indications.…”
Section: Introductionmentioning
confidence: 99%
“…To improve this technical success rate, a pediatric colonoscope [8], a duodenoscope [8,9], and an anterior oblique-viewing endoscope [10,11] have been used instead of the conventional front-viewing enteroscope [12]. Balloon enteroscopy has enabled endoscopists to access the papilla or biliopancreatoenteric anastomoses more definitively and safely [2][3][4][5], and has been commonly performed as the initial attempt to manage several postoperative disorders, in patients with not only Roux-en-Y reconstruction but also prior PD and Billroth II gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In previous articles, the rate of successful ERCP for biliary indications in prior-PD patients was 69-86 % using a front-viewing enteroscope, a pediatric colonoscope, or a duodenoscope [8,9,12]. Owing to the development of the short DBE which has a shorter radius of curvature of the tip of the scope as well as easier and greater maneuverability [13], this rate was increased to 96.7 % (29 of total 30 sessions) in 18 prior-PD patients [2, 5,14].…”
Section: Discussionmentioning
confidence: 99%